(untitled) (PerCursos, 2025)
This article analyzes the challenges to the effective management of Conservation Units (CUs) in the state of Paraíba, based on the guidelines established by Law No. 9.985/2000, which instituted the National System of Nature Conservation Units (SNUC), and Decree No. 4.340/2002, which regulates it. The study adopts a case study methodology, focusing on a Strictly Protected Conservation Unit that was decommissioned (or disestablished / deregistered) due to the absence of effective governance. By legal definition, CUs are territorial spaces with relevant natural resources, established by the government for conservation purposes and subject to a special administrative regime. The research involved bibliometric and documentary analysis, fieldwork, and interviews with environmental managers. The results reveal significant institutional fragility: of the 33 CUs located in Paraíba, approximately 73% lack a management council, and around 82% are without a management plan. These findings underscore the urgency of reassessing management strategies and strengthening the enforcement of the legal framework established by the SNUC.